Development of chemical tools to probe the functions of TRIM proteins - Reynolds, J (2020)
Epigenetic signalling is regulated by ‘writer’, ‘reader’, and ‘eraser’ proteins, which add, identify and remove histone modifications, respectively. Simultaneous recognition of multiple epigenetic marks by proteins containing tandem reader domains increases the complexity of the information transmitted, making these proteins interesting targets for probing epigenetic regulation. Tripartite motif-containing (TRIM) protein 24 and 33 are transcriptional regulators, each containing a C-terminal tandem PHD-bromodomain motif which recognises methylation states and acetylation of modified histone lysine residues. TRIM33 functions within the PARP-dependent DNA damage response pathway, where it is responsible for the timely removal of chromatin-remodelling enzyme ALC1 from sites of DNA damage through its bromodomain. Loss of TRIM33 causes prolonged association of ALC1, and therefore extended chromatin relaxation, which leaves DNA exposed and increases the susceptibility of cells to further DNA damage.